Development of upper tract stones in patients with congenital neurogenic bladder - Stephany, Heidi A. (2013)
OBJECTIVE: Patients with neurogenic bladder are at increased risk of developing upper tract stones. We hypothesized that patients with lower urinary tract stone disease are at greater risk of developing upper tract stones. METHODS: We performed a 10-year retrospective case–control study of patients with neurogenic bladder to determine the association between bladder and upper tract stones. Independent risk factors for upper tract stones were assessed. Cases and controls were matched 1:1. Univariable analysis was performed by Fisher's exact test and the Mann–Whitney U test. Multivariable logistic regression was performed. RESULTS: 52 cases and controls were identified. Cases were significantly more likely to be non-ambulatory, have bowel–urinary tract interposition, thoracic level dysraphism, and history of bladder stones. On multivariable analysis, independent predictors of stone formation were male sex (OR 2.82; p = 0.02), dysraphism involving the thoracic spine (OR 3.37; p = 0.014) bowel–urinary tract interposition (OR 2.611; p = 0.038), and a history of bladder stones (OR 3.57; p = 0.015). CONCLUSION: Patients with neurogenic bladder are at increased risk for upper tract stones. The presence of bladder stones may herald the development of upper tract stones. The predictors of stone disease identified should guide prospective studies to better understand the natural history of upper tract stone development in this population.